2018
DOI: 10.4236/jacen.2018.74014
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Use Efficiencies of Nutrients by Sesame and Bambara Nut Alley Crops as Influenced by Manuring in a Cashew-Based Intercropping System in the Guinea Savanna Agroecology of Nigeria

Abstract: Field experiments were conducted at the experimental farm Cocoa Research Institute of Nigeria (CRIN) Sub-Station, Ochaja, in the Southern Guinea Savannaagro ecological zone of Nigeria to examine uptake and use efficiencies of nutrients by Sesame and Bambara nut alley crops as influenced by manuring in a Cashew-based intercropping system. Experimental treatments were based on responses of sole and intercrop mixtures of Sesame and Bambara nut alley crops to Cocoa Pod Husk (CPH), pelletized organic fertilizer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The un-manured (control) plants had higher N uptake and NHI compared to the fertilizer treated plants. Agele et al (2008) obtained improved NUE for crops under application of organic and inorganic fertilizers, and Rather et al (1999) and Agele et al (2018b) had attributed crop yield increases under fertilizer treatments to improved efficiency of nutrient uptake and use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The un-manured (control) plants had higher N uptake and NHI compared to the fertilizer treated plants. Agele et al (2008) obtained improved NUE for crops under application of organic and inorganic fertilizers, and Rather et al (1999) and Agele et al (2018b) had attributed crop yield increases under fertilizer treatments to improved efficiency of nutrient uptake and use.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in crop responses to inorganic and organic fertilizers can be attributed to differences in nutrient contents, patterns of nutrient release and effects on soil physical, chemical and biological properties (McCall and Willumsen, 1998;Nevens et al, 2004;Agele et al, 2011;Liang et al, 2019). It has been reported that crop species differ in biomass and nutrient uptake, accumulation and partitioning between vegetative and reproductive components (Nevens et al, 2004;Agele et al, 2018b). Differences in uptake, use, accumulation and partitioning of nutrients between vegetative and reproductive components in crop species and varieties are commonly used as criteria for yield selection in crops to develop cultivars adapted to low fertilizer input management systems (Yamoah et al, 1998;Nevens et al, 2004;Agele et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alley intercropping within rows of Cashew plants can recycle nutrients from the deeper layer of the soil and utilize other growth resources because the leaf canopy may not cover quickly [1,2]. However, a successful cultivation 'lag phase' and can also have direct advantages on the initial development of the tree crops [3].…”
Section: Introductionmentioning
confidence: 99%